Decision making tools in regional sanitary landfill location selection - Živković Bojana; Marjanović Jelisaveta; Đokić Jelena (Reciklaža i Održivi Razvoj, 2022)
The paper applies intelligent multicriteria analysis in order to rank the criteria in the process of site selection for the Regional Sanitary Landfill. The analysis was performed for 3 pre-selected sites that were selected based on available area, site access, potential preparation difficulties, groundwater occurrence, biodiversity, and proximity to urban area. These locations were selected as the most suitable for construction, both from the engineering and from the economic and environmental aspect. The analysis is the best example of the application of intelligent multicriteria analysis as a useful tool for environmental management in the decision-making process. The analysis was performed for three proposed locations of the Regional Sanitary Landfill: Kasilo, Kristal, and Savina Stena, in the municipalities of Zvecan and Leposavic. In order to achieve the most objective results, PROMETHEE methods were applied. Using these calculation methods, the following ranking list of locations for the Regional Sanitary Landfill was obtained according to their suitability: Savina Stena, Kasilo, and Kristal. This result can contribute to the decision-making process of determining the development strategy at the local and regional level.